Crime, shame, and reintegration - Braithwaite, John (Cambridge University Press, 1989)
Crime, shame, and reintegration is a contribution to general criminological theory. Its approach is as relevant to professional burglary as to episodic delinquency or white collar crime. Braithwaite argues that some societies have higher crime rates than others because of their different processes of shaming wrongdoing. Shaming can be counterproductive, making crime problems worse. But when shaming is done within a cultural context of respect for the offender, it can be an extraordinarily powerful, efficient and just form of social control.